Pengaruh Bahan Ajar Digital, Kemandirian Belajar, dan Keaktifan Peserta Didik Terhadap Hasil Belajar Mata Pelajaran Praktikum Akuntansi Jasa, Dagang, dan Manufaktur - Argina, Yunia Tri; Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to determine the effect of digital teaching materials, learning independence and activeness on the learning outcomes of accounting practicum for students in class XI AKL SMKN 1 Surabaya. The research is a type of quantitative research by taking a sample of 140 students. The results of data processing through SPSS 25 show that there is a simultaneous influence of teaching materials, independent learning, and activeness on learning outcomes with a significance value < α 0.05. The average level of influence of each variable such as digital teaching materials and activeness has a moderate level of influence and learning independence has a fairly high level of influence on learning outcomes. There is a moderate level of influence due to the utilization of teaching materials that are not optimal and the lack of student focus in learning activities. As well as the need for interest and learning discipline to improve good learning outcomes.